Six-year study on peripheral venous catheter–associated BSI rates in 262 ICUs in eight countries of South-East Asia: International Nosocomial Infection Control Consortium findings. Issue 1 (January 2021) - Rosenthal, Víctor Daniel; Bat-Erdene, Ider; Gupta, Debkishore; Rajhans, Prasad; Myatra, Sheila Nainan; Muralidharan, S; Mehta, Yatin; Rai, Vineya; Hung, Nguyen Viet; Luxsuwong, Montri; Tapang, Audrey Rose D; Guo, Xiuqin; et al.
Background: Short-term peripheral venous catheter–associated bloodstream infection rates have not been systematically studied in Asian countries, and data on peripheral venous catheter–associated bloodstream infections incidence by number of short-term peripheral venous catheter days are not available. Methods: Prospective, surveillance study on peripheral venous catheter–associated bloodstream infections conducted from 1 September 2013 to 31 May 2019 in 262 intensive care units, members of the International Nosocomial Infection Control Consortium, from 78 hospitals in 32 cities of 8 countries in the South-East Asia Region: China, India, Malaysia, Mongolia, Nepal, Philippines, Thailand, and Vietnam. For this research, we applied definition and criteria of the CDC NHSN, methodology of the INICC, and software named INICC Surveillance Online System. Results: We followed 83, 295 intensive care unit patients for 369, 371 bed-days and 376, 492 peripheral venous catheter-days. We identified 999 peripheral venous catheter–associated bloodstream infections, amounting to a rate of 2.65/1000 peripheral venous catheter-days. Mortality in patients with peripheral venous catheter but without peripheral venous catheter–associated bloodstream infections was 4.53% and 12.21% in patients with peripheral venous catheter–associated bloodstream infections. The mean length of stay in patients with peripheral venous catheter but without peripheral venous catheter–associated bloodstream infections was 4.40 days and 7.11 days in patients with peripheral venous catheter and peripheral venous catheter–associated bloodstream infections. The microorganism profile showed 67.1% were Gram-negative bacteria: Escherichia coli (22.9%), Klebsiella spp (10.7%), Pseudomonas aeruginosa (5.3%), Enterobacter spp. (4.5%), and others (23.7%). The predominant Gram-positive bacteria were Staphylococcus aureus (11.4%). Conclusions: Infection prevention programs must be implemented to reduce the incidence of peripheral venous catheter–associated bloodstream infections.